Biohydrogen Production Using Hydrolysates of Palm Oil Mill Effluent (Pome) - Khaleb, N.A; Jahim, J.Md; Kamal, S. Ahmad (Journal of Asian Scientific Research, 2012)
Dark hydrogen fermentation using lignocellulosic biomass has been widely reported. In this study, raw and hydrolysed Palm Oil Mill Effluent (POME) were used as substrates to produce hydrogen by POME sludge in 30-mL serum bottle. A higher cumulative volume of hydrogen of 1439 mL H2.L-1 POME was obtained from hydrolysed POME as compared to raw POME. Fermentation process was then carried out in 2-L stirred tank bioreactor using hydrolysed POME as medium and it was found that a two-fold of hydrogen volumetric rate increase was achieved.